Binding of ArgTX-636 in the NMDA Receptor Ion Channel. Issue 1 (16th January 2015) - Poulsen, Mette H.; Andersen, Jacob; Christensen, Rune; Hansen, Kasper B.; Traynelis, Stephen F.; Strømgaard, Kristian; Kristensen, Anders Skov
Abstract: The N -methyl-d -aspartate receptors (NMDARs) constitute an important class of ligand-gated cation channels that are involved in the majority of excitatory neurotransmission in the human brain. Compounds that bind in the NMDAR ion channel and act as blockers are use- and voltage-dependent inhibitors of NMDAR activity and have therapeutic potential for treatment of a variety of brain diseases or as pharmacological tools for studies of the neurobiological role of NMDARs. We have performed a kinetic analysis of the blocking mechanism of the prototypical polyamine toxin NMDAR ion channel blocker argiotoxin-636 (ArgTX-636) at recombinant GluN1/2A receptors to provide detailed information on the mechanism of block. The predicted binding site of ArgTX-636 is in the pore region of the NMDAR ion channel formed by residues in the transmembrane M3 and the M2 pore-loop segments of the GluN1 and GluN2A subunits. To assess the predicted binding mode in further detail, we performed an alanine- and glycine-scanning mutational analysis of this pore-loop segment to systematically probe the role of pore-lining M2 residues in GluN1 and GluN2A in the channel block by ArgTX-636. Comparison of M2 positions in GluN1 and GluN2A where mutation influences ArgTX-636 potency suggests differential contribution of the M2-loops of GluN1 and GluN2A to binding of ArgTX-636. The results of the mutational analysis are highly relevant for the future structure-based development of argiotoxin-derived NMDAR channel blockers. Graphical abstract: Highlights: The NMDA receptor is an important ligand-gated ion channel in the brain. Small-molecule ligands that bind and block the NMDA receptor ion channel have therapeutic potential for treatment of brain diseases. We examine the mechanism of block for the spider polyamine toxin argiotoxin-636 at the GluN1/2A-type NMDA receptor. Argiotoxin-636 is a fast binding and unbinding trapping blocker of GluN1/2A receptor. Mutational analysis of M2-loop segments in GluN1/2A identifies residues important for argiotoxin-636 block.